2019
DOI: 10.1111/trf.15541
|View full text |Cite
|
Sign up to set email alerts
|

Association of donor age, body mass index, hemoglobin, and smoking status with in‐hospital mortality and length of stay among red blood cell–transfused recipients

Abstract: BACKGROUND: Recent publications have reported conflicting findings regarding associations of blood donor demographics and mortality of transfused patients. We hypothesized that the analysis of additional donor characteristics and consideration of alternative outcomes might provide insight into these disparate results. STUDY DESIGN AND METHODS:We analyzed data from a retrospective cohort of transfused patients from the Recipient Epidemiology and Donor Evaluation Study-III (REDS-III). We used stratified Cox regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
(149 reference statements)
0
21
0
Order By: Relevance
“…Although substantial engineering and testing would be needed, in principle the presented strategy could be adapted to an inexpensive laser-free imaging flow cytometer for resource-poor situations. Improved techniques to monitor blood product quality would revolutionize efforts to personalize allocation of blood products based on factors thought to impact RBC quality, including donor characteristics (age, sex, ethnicity, frequency of donation) ( 44 , 46 50 ). Like many artificial-intelligence–driven analysis systems introduced in recent years, the goal need not be to entirely eliminate expert interaction but instead to screen samples or cell images to identify the most readily classifiable, so that the expert’s time is used on samples or cells that are more borderline.…”
Section: Discussionmentioning
confidence: 99%
“…Although substantial engineering and testing would be needed, in principle the presented strategy could be adapted to an inexpensive laser-free imaging flow cytometer for resource-poor situations. Improved techniques to monitor blood product quality would revolutionize efforts to personalize allocation of blood products based on factors thought to impact RBC quality, including donor characteristics (age, sex, ethnicity, frequency of donation) ( 44 , 46 50 ). Like many artificial-intelligence–driven analysis systems introduced in recent years, the goal need not be to entirely eliminate expert interaction but instead to screen samples or cell images to identify the most readily classifiable, so that the expert’s time is used on samples or cells that are more borderline.…”
Section: Discussionmentioning
confidence: 99%
“…While self‐reported smoking may underestimate its true prevalence, rates of smoking in donors (6.4%) paralleled those of transfused recipients in our study. However, this rate was lower than in prior studies, increasing the possibility of a chance result (Type I error) related to the study of infrequent events (the combination of donor smoking and gamma irradiation) on transfusion outcomes . The small number of gamma irradiated RBC units from smokers (approx.…”
Section: Discussionmentioning
confidence: 75%
“…A retrospective cohort study of 93,726 patients in the REDS-III program showed that hospital length of stay was lower for the recipients of RBC units from young donors (<20 years old) [ 81 ]. Analysis of data separately for female and male RBCs gave a similar result.…”
Section: Red Blood Cellsmentioning
confidence: 99%
“…Analysis of data separately for female and male RBCs gave a similar result. The effect was deemed small and appeared when four or more units of RBCs were transfused [ 81 ]. Inflammatory markers change with age, and this can be investigated further in relation to the apparently favorable outcomes from the transfusion of young donor’s RBCs [ 81 ].…”
Section: Red Blood Cellsmentioning
confidence: 99%
See 1 more Smart Citation